Listening to voices: understanding and self-management of auditory verbal hallucinations in young adults. Issue 3 (3rd July 2022) - Denno, Peter; Wallis, Stephanie; Caldwell, Kimberly; Ives, Jonathan; Wood, Stephen J.; Broome, Matthew R.; Mallikarjun, Pavan; Oyebode, Femi; Upthegrove, Rachel
ABSTRACT: Background: Auditory Verbal Hallucinations (AVH) are a hallmark of psychosis, but affect many other clinical populations. Patients' understanding and self-management of AVH may differ between diagnostic groups, change over time, and influence clinical outcomes. This study aimed to explore patients' understanding and self-management of AVH in a young adult clinical population. Methods: 35 participants were purposively sampled from a youth mental health service. Participants completed diary and photo-elicitation tasks, and the resulting materials were discussed at in-depth interviews. Themes were derived using conventional content analysis. Results: Three themes emerged. (1) Searching for answers, forming identities – voice-hearers sought to explain their experiences, resulting in the construction of identities for voices and themselves. Explanations were drawn from participants' life-stories and belief-systems. (2) Coping goals – patients' self-management strategies were diverse, reflecting the diverse negative experience of AVH, e.g. as distressing sounds, overwhelming emotions, or as threats to agency. (3) Outlook – participants formed an overall outlook on their life with AVH. Resignation and hopelessness in connection with disabling AVH are contrasted with "acceptance" or integration, described as positive, ideal, or mature. Discussion: Trans-diagnostic commonalities in understanding and self-management of AVH are highlighted. These offer targets for individual therapies and further research.